Методи нормаліації зображень афіної та проєктивної групи перетворення - Фролов, Д. Є. (ХНУРЕ, 2025)
Image processing methods are becoming more and more important every year. They facilitate automation, increase the efficiency of visual data analysis, and stimulate the development of new technologies. The development of new methods for object recognition and image normalization is a pressing issue in computer vision and image processing. Normalization methods are divided into two groups. These are the affine and projective groups. Depending on the appli-cation, normalization methods of the affine or projective group are used.
Keywords: нормалізація зображень; афінна група; проєктивна група